Peramalan Prevalensi Tuberkulosis Provinsi Jawa Barat Menggunakan Model ARIMA - Venita Syavera; Diara Winanda (Griya Journal of Mathematics Education and Application, 2026)
Tuberculosis (TB) remains a major public health problem in Indonesia, with West Java Province contributing the largest share of national cases. Understanding temporal dynamics of TB cases is essential to support disease control planning. This study aims to analyze the temporal pattern and short-term forecasting of tuberculosis cases in West Java Province using the Autoregressive Integrated Moving Average (ARIMA) model. Secondary time-series data of TB cases from all districts and cities in West Java during the period 2019-2023 were used and aggregated at the provincial level. Model identification was conducted through stationarity testing and analysis of autocorrelation and partial autocorrelation functions. The best-performing model was selected based on information criteria and residual diagnostics. The results indicate that ARIMA(1,1,1) is the most suitable model for representing the temporal dynamics of TB cases. Forecasting results for the next six months show a relatively stable trend without extreme fluctuations, although the predicted number of cases remains high, particularly in densely populated urban areas such as Bogor Regency, Bandung City, and Depok City. These findings demonstrate that ARIMA provides a simple yet effective approach for short-term forecasting of TB cases and can support provincial-level planning and decision-making in tuberculosis control programs.